Digital-Based PAI Learning Strategy in Increasing Student Learning Motivation at SMP 12 Tasikmalaya City - Syarifah, Annisa; Maulana Restu, Yanto; Fuad Hilmi, Riza; Tsamrotul Fauziah, Zahroh (CV Kalimasada Group, 2025)
Purpose - This article discusses various strategies in Islamic religious education aimed at developing the spiritual, moral, and intellectual understanding of students. Islamic religious education not only focuses on the aspect of religious knowledge but also on the formation of character that reflects Islamic values, such as honesty, patience, and social responsibility. Some of the strategies used include experiential learning, interactive discussions, the use of digital media, and contextual approaches relevant to daily life. Islamic religious education also emphasizes the importance of role models from educators, a conducive educational environment, and support from family and community. Through these strategies, students are expected not only to master the subject matter but also to practice Islamic values in their lives. Design/Methodology/Approach - This study uses qualitative methods, which aim to find as much information as possible about digital-based PAI learning strategies in improving student learning motivation at SMP 12 Tasikmalaya City. Findings -This article highlights that a holistic approach to Islamic religious education is essential to shaping a generation that is not only intellectually intelligent but also morally upright. Originality/Value - This article emphasizes the importance of teacher training to ensure they can effectively use technology, as well as the need for improved technological facilities in schools. At SMP 12 Kota Tasikmalaya, the use of digital-based learning remains limited due to infrastructure constraints.